Underweight was associated with increased mortality in adults with latent tuberculosis infection - Liao, Jun-Zhe; Liu, Xiao; Qi, Min (Frontiers in Nutrition, 2025)
ObjectiveLatent tuberculosis (TB) infection (LTBI) is a reservoir for active TB. Although body mass index (BMI) predicts LTBI progression and influences active TB outcomes, its association with mortality in LTBI patients remains unclear. We therefore investigated this relationship in a US cohort.Research methods & proceduresData from the National Health and Nutrition Examination Survey 2011–2012 was utilized. Survival differences across BMI categories were assessed with Kaplan–Meier curves and multivariable Cox regression. The Restricted Cubic Spline (RCS) analysis modeled the nonlinear relationship between BMI and mortality risk.ResultsAmong 700 LTBI participants analyzed, multivariable Cox regression identified underweight individuals as having higher mortality risk than normalweight counterparts (adjusted HR = 2.77, 95% CI 1.06–7.22, p = 0.04). No significant mortality associations were observed for obese or overweight participants across both crude and adjusted models (all p > 0.05). RCS analysis demonstrated a U-shaped pattern between BMI and mortality, with minimum mortality risk at BMI 27.3 kg/m2 (p for nonlinearity = 0.0012).ConclusionIn LTBI adults, underweight status independently predicted increased mortality risk, while overweight or obesity showed no association. RCS analysis confirmed a U-shaped BMI-mortality relationship with optimal survival at 27.3 kg/m2.